The Correlation of the Ability to Read With a Elementary School - Setianti, Tiyas Puji; Hartati, Tatat (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The ability to read and write is a tool of communication between a person and others. In recent years these two abilities have become a hot topic among academics to improve the quality of both abilities, considering that both of them have poor rankings. But the training of these two skills often uses two methods without being integrated. This study aims to see the correlation between reading and writing skills so that it can be a reference for teachers in determining methods to teach reading and writing simultaneously. Reviewing the correlation of two variables, using experimental methods, correlational types, and using Pearson's test. Samples were taken incidentally with a non-probability sampling technique. The result shows a sig. of 0.16 and a positive value with a value of 0.350. This means that the ability to read and write early correlates. If a person's reading ability is good, then his writing ability will be good.